Structure of the human protein kinase MPSK1 reveals an atypical activation loop architecture. - Eswaran, J; Bernad, A; Ligos, J; Guinea, B; Debreczeni, J; Sobott, F; Parker, SA; Najmanovich, R; Turk, B; Knapp, S (2008)
The activation segment of protein kinases is structurally highly conserved and central to regulation of kinase activation. Here we report an atypical activation segment architecture in human MPSK1 comprising a beta sheet and a large alpha-helical insertion. Sequence comparisons suggested that similar activation segments exist in all members of the MPSK1 family and in MAST kinases. The consequence of this nonclassical activation segment on substrate recognition was studied using peptide library screens that revealed a preferred substrate sequence of X-X-P/V/I-phi-H/Y-T*-N/G-X-X-X (phi is an aliphatic residue). In addition, we identified the GTPase DRG1 as an MPSK1 interaction partner and specific substrate. The interaction domain in DRG1 was mapped to the N terminus, leading to recruitment and phosphorylation at Thr100 within the GTPase domain. The presented data reveal an atypical kinase structural motif and suggest a role of MPSK1 regulating DRG1, a GTPase involved in regulation of cellular growth.